Starting Right: A Basic Guide to Museum Planning - George, Gerald; Maryan-George, Carol (Rowman & Littlefield Publishers, 2012)
Are you thinking of starting a museum? Starting Right has been helping non-professionals learn the basics of museum planning for nearly three decades. This fully-revised, third edition will help you understand what you are getting into, evaluate prospects, avoid pitfalls, and take advantage of many kinds of available help. Addressing current and perennial issues facing new museums, from digital technologies to fund raising concerns, Starting Right takes you step-by-step through the process of creating a sound plan for starting your museum.